(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
This essay analyses Paolo Sorrentino’s production from the perspective of the compilation soundtracks he assembles for his films. While “La grande bellezza” appears to synthesize many of the aspects of a patchwork of different songs, the overall compilation resulting from Sorrentino’s entire filmography is singularly interesting (from the song “I migliori anni della nostra vita” in “Il divo” and “Che domenica bestiale” in “Loro 1” through to “Senza un perché” in “The Young Pope”, to name but a few). This composition strategy – a playlist, in a sense – reveals a clear authorial stamp, a signature,displaying clear elements of continuity with a form of American cinema (from Quentin Tarantino to Paul Thomas Anderson), and, at the same time, a systematic approach that differs from the majority of Italian cinema (first and foremost the work of Nanni Moretti and Paolo Virzì), which requires more prudent scholarly attention.